2003
DOI: 10.1103/physreve.68.041913
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization between main rhythmic processes in the human cardiovascular system

Abstract: For the cases of spontaneous respiration and paced respiration with a fixed frequency and linearly increasing frequency, we investigate synchronization between three main rhythmic processes governing the cardiovascular dynamics in humans, namely, the main heart rhythm, respiration, and the process whose fundamental frequency is close to 0.1 Hz. The analysis of the experimental records reveals synchronous regimes of different orders n:m between all the three main rhythms. The influence of the regime of breathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
70
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 26 publications
4
70
0
6
Order By: Relevance
“…Though the characterization of the new intermittent process has been here explicitly derived at the boundary of phase synchronization of chaotic systems, we expect that the very same mechanism can be observed in many other relevant circumstances, as e.g. laser systems [11], or in the case of the interaction between the main rhythmic processes in the human cardiovascular system [20,21].…”
mentioning
confidence: 99%
“…Though the characterization of the new intermittent process has been here explicitly derived at the boundary of phase synchronization of chaotic systems, we expect that the very same mechanism can be observed in many other relevant circumstances, as e.g. laser systems [11], or in the case of the interaction between the main rhythmic processes in the human cardiovascular system [20,21].…”
mentioning
confidence: 99%
“…E 73, 026208 (2006) † Electronic address: aeh@cas.ssu.runnet.ru ‡ Electronic address: alkor@cas.ssu.runnet.ru § Electronic address: vip@sgu.ru in the human CVS has been reported in Refs. [5,9,10,11,12]. It has been found that the systems generating the main heart rhythm and the rhythm of slow regulation of blood pressure can be treated as self-sustained oscillators and the respiration can be regarded as an external forcing of these systems [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[5,9,10,11,12]. It has been found that the systems generating the main heart rhythm and the rhythm of slow regulation of blood pressure can be treated as self-sustained oscillators and the respiration can be regarded as an external forcing of these systems [11,12]. However, at respiration frequencies close to 0.1 Hz it becomes difficult to distinguish the case of true synchronization between the respiration and the process of blood pressure regulation from the case of spurious synchronization caused by the presence of the respiratory component in the HRV and blood pressure signals used for the analysis of the rhythm with the basic frequency of about 0.1 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…1). Earlier studies have focused on short data segments to identify certain degrees of cardiorespiratory phase synchronization (CRPS) in healthy young subjects (5,6) and in newborn infants (7). A more recent study has identified an intriguing effect of maternal-fetal heartrate synchronization (8).…”
mentioning
confidence: 99%